PENGURANGAN RISIKO BENCANA BERBASIS DESTANA DI DESA GLAGAHARJO DALAM MEWUJUDKAN KETAHANAN WILAYAH KABUPATEN SLEMAN - Lexi Jalu Aji; Siswo Hadi Sumantri; Yuli Subiakto; Annisa Rahmawati (Jurnal Manajemen Bencana (JMB), 2022)
Glagaharjo Village is a one of the villages in Sleman Regency that is a Disaster Resilient Village (DRV). This study aims to analyze the implementation of disaster risk reduction based on disaster resilient village in Glagaharjo Village and its implications for regional resilience in Sleman Regency. Using a qualitative method with an exploratory approach, the research was conducted from May 2021 - January 2022 in Glagaharjo Village, Cangkringan District, Sleman Regency. Interviews, documentation, and observation with analytical techniques using the Miles, Huberman and Saldana model were used as the data collection techniques. The result of this research shows that disaster risk reduction based on disaster resilient village in Glagaharjo Village has successfully met the criteria to become a Major Disaster Resilient Village by getting a score of 98/112. Consequently, the program has fulfilled the Astagatra aspect and has positive implications for regional resilience in Sleman Regency, as it supports 6 of 7 priorities for regional resilience, namely: (1) strengthening policies and institutions, (2) risk assessment and integrated planning, (3) developing information systems, training and logistics, (4) handling thematic areas prone to disasters, (5) disaster emergency preparedness and handling, and (6) development of disaster recovery system.